Edukasi dan Pemeriksaan Kesehatan Di Wilayah Pimpinan Cabang Asiyiyah Cengkareng - Asti Al Hikmah; Ibnu Salis Fitra; Mellisa Kasim; Muhammad Hendrawan Ramadhani; Refina Oktavia (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Increased life expectancy and behavioral changes and demographic transitions trigger epidemiological transitions. The World Health Organization (WHO) declared 2020-2030 the "Decade of Healthy Aging". Hypertension and diabetes mellitus are two of the most common non-communicable diseases and are associated with high morbidity and mortality. The method carried out in this activity is by conducting health checks, namely checking blood pressure and blood sugar and counseling to each individual after the examination. The relationship between the incidence of hypertension and diabetes mellitus according to some researchers is very closely related, therefore we, carry out health examination and education work programs for the community, staff and teachers in the West Cengkareng output area and PCA Cengkareng aimed to increase public awareness in maintaining health. From the health examination activities, it is hoped that the people of the PCA area and West Cengkareng Village can maintain a healthier lifestyle, for their physical and spiritual health. Based on the Real Work Lecture (KKN) activity in the form of a health check, this has benefits where the community can do health checks for free, and the community gets new knowledge related to the application of a healthy lifestyle in maintaining their body health.